2016
DOI: 10.1186/s13063-015-1105-3
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ willingness to participate in clinical trials and their views on aspects of cancer research: results of a prospective patient survey

Abstract: BackgroundRecruitment to clinical trials can be challenging and slower than anticipated. This prospective patient survey aimed to investigate the proportion of patients approached about a trial who agree to participate, their motivations for trial participation and their views on aspects of cancer research.MethodsPatients who had been approached about participation in any clinical trials in the Gastrointestinal and Lymphoma Unit at the Royal Marsden were invited to complete a questionnaire. The statistical ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
145
2
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(174 citation statements)
references
References 35 publications
21
145
2
6
Order By: Relevance
“…The high survey completion rate (91%) is consistent with the idea that patients recognise the benefits of medical research and are keen to engage with the research community as reported by Moorcraft et al . A key finding of our study was that almost half the participants assumed their medical data were already being used for research purposes without prior consent, a finding which supports previous smaller studies .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The high survey completion rate (91%) is consistent with the idea that patients recognise the benefits of medical research and are keen to engage with the research community as reported by Moorcraft et al . A key finding of our study was that almost half the participants assumed their medical data were already being used for research purposes without prior consent, a finding which supports previous smaller studies .…”
Section: Discussionsupporting
confidence: 87%
“…A key strength of this study is the sample size, which is the largest reported in this field, and the diversity and potential generalisability of its sample population. Thirty‐three percent of participants in this study were of European descent, higher than that of the Moorcraft ( n = 276) and Kaufman ( n = 451) studies (14% and 20% respectively). More than half the participants preferred an opt‐out approach compared to the conventional opt‐in method and support for an opt‐out model was comparable between different age groups, genders, employment status and cognitive ability.…”
Section: Discussionmentioning
confidence: 60%
“…This study showed that many HNC and LC survivors started the intervention for extrinsic reasons. Altruism is common among cancer patients who participate in research [2628]. However, there were also patients who started the intervention for intrinsic reasons.…”
Section: Discussionmentioning
confidence: 99%
“…Although most cancer patients do not participate in cancer trials, most of those who are approached to do so, do not decline to participate (Van Der Biessen,2013;Catt, Langridge, Fallowfield, Talbot, Jenkins, 2011; Moorcraft , Marriott, Pecket, et.al., 2016). For this reason, it has proven difficult for researchers to study decliners.…”
Section: Discussionmentioning
confidence: 99%